The complete mitogenome of Pareuchiloglanis sichuanensis (Siluriformes: Sisoridae). Issue 10 (3rd October 2021) - Yan, Taiming; Zhang, Qian; He, Jiayang; Yan, Feiyang; Ma, Zhijun; Chen, Hongjun; Ye, Lijuan; Zhang, Nan; Yang, Deying; He, Zhi
Abstract: Pareuchiloglanis sichuanensis is an endemic fish species in the upper reaches of the Yangtze River. In the present study, the complete mitochondrial genome of P. sichuanensis was analyzed. The mitochondrial genome, consisting of 16, 774 base pairs (bp), included 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a non-coding control region. The phylogenetic tree showed that P. sichuanensis was closely related to P. anteanalis . These results provid the useful information for further studies on taxonomic status, molecular systematics, and stock evaluation.